Effect of shielding on pelvic and abdominal ioert dose distributions. (September 2016) - Esposito, Alessandro; Sakellaris, Taxiarchis; Limede, Patrícia; Costa, Filipa; Cunha, Luis T.; Dias, Anabela Gregório; Lencart, Joana; Sarmento, Sandra; Rosa, Carla Carmelo
Abstract : Introduction: Intra-Operative Electron Radiation Therapy (IOERT) uses high-energy electron beams to irradiate the tumour bed during surgery, while healthy tissues are shielded or moved away. Monte Carlo (MC) simulations are a powerful tool to study the dosimetric effects of shields, with high level of detail and visualization. Purpose: To obtain graphical and quantitative evaluations, which can be used by radiation oncologists to optimize the use of shielding during pelvic and abdominal IOERT. Materials and methods: For this work, an adapted LINAC Varian CLINAC 2100CD was used. The IOERT model was built on the basis of Varian MC Package using BEAMnrc and EGSnrc, and assessed by Gamma analysis (2%, 2 mm). The minimum lead thickness required for an efficient shield was determined and several shielding configurations were simulated to build a set of clinically relevant scenarios. The effect of bone beneath the shielded tissue was studied. Results: 98% of Gamma points <1 in reference and non-reference conditions proved the reliability of IOERT model. A lateral hot-spot is a consequence of insufficient shielding. Sufficient shield thickness ensures consistent dose reduction near the surface, but lateral scattering phenomena enlarge the dose distribution deeper in the phantom. This effect is more relevant when a bevelled applicator is used. The presence of bone reduces the magnitude of this effect. Conclusion: Radio-oncologists need to be aware of the effect of lateral scattering when using shielding and bevelled applicators. Since lateral scattering is independent from shield thickness, only a geometrical rearrangement can minimize this effect. Disclosure: The authors have no relevant financial or non-financial relationships to disclose.